The diagnostic water governance tool − supporting cross-sectoral cooperation and coordination in water resources management. Issue 140 (February 2023) - Stein, Ulf; Bueb, Benedict; Knieper, Christian; Tröltzsch, Jenny; Vidaurre, Rodrigo; Favero, Fausto
Abstract: In the search for solutions for Integrated Water Resources Management (IWRM), decision-makers frequently face governance-related challenges such as the fragmentation of institutions, the interconnection with other essential services and overlapping competences. In many cases, solutions to these challenges involve strengthening coordination between different actors and sectors. Today different digital tools and resources are available to support related decision-making processes. These tools can (1) offer a context-specific assessment of the water governance system ("Diagnosis") and (2) provide, in some cases, context-specific recommendations to tackle identified deficits ("Therapy"). In this paper, we aim to advance the understanding of the potential of digital tools for water governance and management assessments. After reviewing relevant tools, we introduce the Diagnostic Water Governance Tool (DWGT) that builds on a clear diagnosis-therapy-logic. After presenting the empirical basis and functional logic of the DWGT, we test the DWGT in two case studies: the Guadalquivir river basin in Spain and the Emscher river basin in Germany. We find that the DWGT provides context-specific, evidence-based instrument recommendations that can enhance water governance and management, albeit accompanying suitability evaluations by governance experts remain critical. We conclude by discussing the limitations of digital tools for water governance and management assessments and sketch out fields of future research. Highlights: Most water governance online tools do not allow for case-specific assessments. Diagnostic Water Governance Tool identifies context-specific coordination deficits. The Tool gives case-sensitive recommendations for governance instruments. Fuzzy set Qualitative Comparative Analysis provides sound methodological framework. The Tool's analysis can supplement but not replace expert evaluations.